Evolution of the Norwegian plateau icefield Hardangerjøkulen since the 'Little Ice Age'. (December 2019) - Weber, Paul; Boston, Clare M; Lovell, Harold; Andreassen, Liss M
The maximum 'Little Ice Age' (LIA) glacier extent provides a significant baseline to assess long-term glacier change and to place currently observed rates of glacier recession in a broader temporal context. To that end, we examine the evolution of the plateau icefield Hardangerjøkulen since the LIA. First, we reconstruct Hardangerjøkulen's maximum LIA extent (~AD 1750) and subsequent recession based on the glacial landform record and aided by historical map interpretation. Ice-marginal moraines, glacial drift limits, trimlines, and identifiable erosion and weathering boundaries provide evidence of a LIA icefield with an area of 110 km 2 . Existing LIA model simulations of Hardangerjøkulen are not yet fully able to reproduce our reconstructed extent. Second, we compile a set of remotely sensed icefield outlines from successive time points in the 20th and 21st century to calculate icefield area and length change since the LIA. This reveals a substantial reduction in icefield size, with a total area loss of 41 km 2 (37%; 2% 10 a –1 ) by 2010 and a cumulative frontal retreat averaging 1.3 km (29%; 5 m a –1 ) by 2013. Icefield recession has been greatest since the end of the 20th century, when rates of areal shrinkage increased to 6.5–10% 10 a –1 in 1995–2010, and the rate of average terminus retreat accelerated to 17 m a –1 in 2003–2010. Third, we present a relative dating approach, based on the known age of the different icefield outlines, that allows bracketing ages to be assigned to all ice-marginal landforms between any two outlines. This approach shows that episodes of moraine formation vary temporally between individual outlet glaciers of Hardangerjøkulen, suggesting that the moraine record of a single outlet glacier alone may not be sufficient to derive an icefield-wide picture of past ice advances, and thereby climate fluctuations.